PENGAWASAN PEMERINTAH DAERAH DALAM PENDISTRIBUSIAN GAS LPG 3KG DI KABUPATEN SIDENRENG RAPPANG - Yusriadi; Jabbar, Abdul; Barisan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to describe and analyze local government supervision in the distribution of 3kg lpg gas in Sidenreng Rappang Regency. This study used descriptive qualitative with 8 informants as data sources and data analysis using Nvivo 12 Software. The results of this study show that local government supervision in the distribution of 3kg LPG gas has been implemented quite well in supervising the steps in supervising inspection and monitoring prices, stock availability, and completeness of documents. two indicators of Sarwoto's theory of supervision (2003; 93) which has been run by the Head of the Economic and Natural Resources Section, and the Trade and Industry Office, as well as the 3kg LPG Gas Agent and Base has been carried out quite well.